2022
DOI: 10.1007/s00775-022-01931-w
|View full text |Cite
|
Sign up to set email alerts
|

Major trace elements and their binding proteins in the early phase of Covid-19 infection

Abstract: Metal ions seem to play important roles in the pathogenesis of the novel coronavirus disease of 2019 and are under investigation as potential prognostic markers and supplements in therapeutic procedures. The present study was aimed at assessing the relationship between the most abundant essential microelements (iron, zinc and copper) and their major binding proteins in the circulation in the early stage of infection. The concentration of zinc ions was measured to be higher in infected than in healthy persons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Regarding the results of the AlphaFoldDB dataset, macrophage mannose receptor 1 (MRC1) 48 , Thyroglobulin (TG) 49 , contactin-associated protein-like 3 (CTNNAP3) 50 , Hypoxia up-regulated protein 1 (HYOU1) 51 are top entries with reported relationships to the virus. The method again ranks members of alpha-2-macroglobulin/complement 3 protein family (A2M/C3) 52 in high order: pregnancy zone protein (PZP) 53 , CD109 antigen and Alpha-2-macroglobulin 54 , which appears in the results of both human protein datasets. The selected candidates from these datasets share similarities in protein 2D/3D/chemical structure and transcript sequence, as observed in the results of the viral dataset (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the results of the AlphaFoldDB dataset, macrophage mannose receptor 1 (MRC1) 48 , Thyroglobulin (TG) 49 , contactin-associated protein-like 3 (CTNNAP3) 50 , Hypoxia up-regulated protein 1 (HYOU1) 51 are top entries with reported relationships to the virus. The method again ranks members of alpha-2-macroglobulin/complement 3 protein family (A2M/C3) 52 in high order: pregnancy zone protein (PZP) 53 , CD109 antigen and Alpha-2-macroglobulin 54 , which appears in the results of both human protein datasets. The selected candidates from these datasets share similarities in protein 2D/3D/chemical structure and transcript sequence, as observed in the results of the viral dataset (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Although the plasma concentrations of these trace elements were shown to change during the majority of infections, it is still unclear whether the infected tissues (i.e., the liver) experience the same alteration [65]. It is believed that the activity of HBV is altered by the change of the serum levels of these major trace elements [19]. However, the variation of plasma levels of trace elements in viral infections and their effect on creating a tissue injury is still unknown [3].…”
Section: Roles and Mechanism Of Trace Elements In Chronic Hepatitismentioning
confidence: 99%
“…Studies have been recently conducted and indicated the benefits of using micronutrients as a natural approach to manage the infectious diseases that affect the respiratory system [18][19][20][21]. Given the current COVID-19 pandemic, which has a high mortality rate, particularly in critically ill patients [12], many studies have been conducted to distinguish the different clinical symptoms; however, the data concerning its pathology as well as the cellular responses to this virus are still limited [22].…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of trace elements could affect innate and adaptive immune response, which predisposes to infections and further aggravates malnutrition (11). At present, there are also a number of studies and reviews highlighting a potentially important roles of trace elements in the pathogenesis of COVID-19, and investigating the possibility of utilization of trace elements in diagnosis, prognosis and supplements in therapeutic procedures (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%